Development communication in the Ciliwung Bersih movement - Hidayaturahmi, Hidayaturahmi; Lubis, Djuara P; Adiwibowo, Soeryo; Kartodihardjo, Hariadi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study identifies the role of the Clean Ciliwung Movement (GCB) in the management of the Ciliwung river and how the communication model is built in driving community participation. The method used in this study is descriptive qualitative with data collection techniques through interviews with selected informants, namely from GCB administrators and communities that are members ofciliwung community activists spread across the upstream, middle, and downstream areas of the Ciliwung river. Out of a total of 36 communities that are partners of the GCB, this study took 9 communities representing the three segments of the Ciliwung river. Based on the data obtained, this study found that the role of GCB in managing the Ciliwung river was carried out by focusing on programs that involved partnership programs with stakeholder elements including: government, private sector, community communities, academics, non-governmental organizations, and international institutions. In implementing this program, GCB develops a development communication strategy with an emphasis on community empowerment, namely through network development, competency development, advocacy, and community organizing.